Groundwater vulnerability and, risk assessment of seawater intrusion for the development of a strategy plan towards sustainability: Case of the Souss-Massa coastal area, Morocco - Yassine Ez-zaouy; Lhoussaine Bouchaou; Mohammed Hssaisoune; Abdelhaq Aangri; Gianluigi Busico; Saadou Oumarou Danni; Oumaima Attar; Mohamed Nehmadou; Aicha Saad; Yassine Ait Brahim (Journal of Hydrology: Regional Studies)
Study region: The downstream part of the Souss-Massa Basin, Central Western part of Morocco, Northwestern Africa. Study focus: The Souss-Massa coastal area (SMCA) is known for tourism, fishing, and agriculture activities, which require intensive pumping of groundwater. This situation exacerbates aquifer depletion, reduce groundwater quality, and leads to seawater intrusion. Hence, the investigation of vulnerability and risk of seawater intrusion became a priority in the SMCA. An improved GALDIT (composed by nine parameters: groundwater occurrence (G), hydraulic conductivity (A), groundwater above sea level (L), distance from the shore (D), impact of existing status of sea water intrusion (I), thickness of the aquifer (T), river contribution (R), hydraulic gradient (HG), detected and probable seawater intrusion (DPSWI) was applied in the study area using Analytical Hierarchy Process (AHP) and Sensitivity Analysis (SA) to map groundwater vulnerability to seawater intrusion (GWVSI). Moreover, the risk map of seawater intrusion has been created through the combination of the groundwater vulnerability map and the Water Quality Index map (WQI). Our results show that improved GALDIT provides a better overview on groundwater vulnerability to seawater intrusion in comparison to the standard approach. The study area has five levels of vulnerability, very low, low, moderate, high, and very high, which present 15 %, 1.3 %, 19.8 %, 5.5 %, and 58.4 %, respectively. The risk map indicates five levels (low, moderate, high, very high, and extreme), with the southwestern area being the most exposed to the risk of marine intrusion. Finally, the results of this study have been validated using mapped seawater intrusion, and groundwater quality index (GQIsw). Based on the results, we propose a management plan to preserve and manage the coastal aquifer of the Souss-Massa basin.